The Effect of Oxygen Inhalation Plus Oxytocin Compared with Oxytocin Only on Postpartum Haemorrhage: A Randomized Clinical Trial - Suhrabi, Zainab (J Clin Diagn Res, 2016)
INTRODUCTION: Post Partum Haemorrhage (PPH) is the leading cause of maternal mortality across the world, mainly in the developing countries. AIM: The present study was conducted with the aim to investigate effect of oxygen inhalation plus oxytocin compared with oxytocin only on PPH. MATERIALS AND METHODS: This study was a clinical trial which was performed in Shahid Mustafa Khomieni Teaching Hospital of Ilam (western Iran) from April 2012 to Nov 2013. One hundred and twenty pregnant women who were referred to delivery ward for normal vaginal delivery were selected with convenience sampling method and they were randomly assigned into two groups. For both groups management of the third stage of labour was done using 1000CC Ringer and 20 units of Oxytocin. In the intervention group, in addition to the routine administration, 8 liters of oxygen via face mask was used continuously until 2 hours after delivery. Blood loss was determined by regular weighing of the buttocks that were previously weighted. The difference was calculated before and after weighing (1 gram increasing of weight was considered to be equivalent to 1CC blood loss). Data were analysed by SPSS 16 version using Student- t and Chi-square tests. RESULTS: The two groups were homogenous in regard to all the base line variables. The study results indicated that the mean of blood loss were (256.16±97) ml at two hours after delivery in the control group and (149.5±46.49) ml in the intervention group. There was a significant difference between PPH of the two groups (p<0.006). CONCLUSION: Research findings showed that the use of inspired oxygen during the third stage of labour and oxytocin infusion during 2hours later resulted in a significant decreasing in the amount of bleeding after normal vaginal delivery.